Analysis of Differences in Company Financial Performance Before and After Mergers or Acquisitions in Companies Carrying out a Merger or Acquisition on the Indonesian Stock Exchange 2019-2021 Period - Rizka Destiana; Nur Amyza (Riviera Publishing, 2024)
In the world of capital markets, the influence of investment is very influential. Mergers and acquisitions are considered one of the most efficient ways to gain access to new markets or enhance the capabilities necessary to face the world's challenges. The purpose of this study is to prove whether there is a difference in 9 financial ratios consisting of NPM, ROA, ROE, CR, QR, DR, TATO, EPS, and EVA before and after the merger or acquisition. This study is quantitative research; the assessment of the company's financial performance in this study uses financial statements 1 year before and 1 year after the merger or acquisition. The sample used in this study includes all companies that go public that carry out mergers or acquisitions on the Indonesia Stock Exchange for the 2019-2021 period. Sampling was conducted using the purposive sampling method so that 26 companies that carried out mergers or acquisitions were obtained. The analysis methods used were descriptive statistical tests, the One-Sample Kolmogorov Smirnov Test normality test, and the Wilcoxon Signed Rank Test differentiated tests. The results in this study showed that there was no difference in the variables NPM, ROA, ROE, CR, QR, DR, TATO, and EPS before and after the merger or acquisition, while there was a difference in EVA before and after the merger or acquisition.